Indagar dibujando - Rodríguez, Nélida B. (2018)
The value of the drawing as an instrument to represent what is known, defined, existing, is enriched when considering its potential to investigate, to explore and reduce the uncertainty inherent in the design process. Addressing the drawing as an instrument of inquiry implies not focusing its approach on the representation, without removing that historical merit, still current and necessary. It is to consider that its instrumental value facilitates the creative process of design, makes it possible to "think drawing". Drawing as an instrument of inquiry has as its main objective to enhance the development of the ability to think spatially.